Long‐term therapeutic effect of cell therapy on improvement in erectile function in a rat model with pelvic neurovascular injury. (27th February 2019) - Gu, Xin; Shi, Hua; Matz, Ethan; Zhong, Liren; Long, Ting; Clouse, Cara; Li, Wei; Chen, Dong; Chung, HyunChul; Murphy, Sean; Yoo, James; Lin, Guiting; et al.
Abstract : Objective: To determine the long‐term therapeutic effect amongst three human cell types on erectile function recovery in a rat model of dual neurovascular‐injury erectile dysfunction (NVED). Materials and methods: A dual NVED model was established in athymic rats by crushing the bilateral cavernous nerves and ligating the bilateral internal pudendal neurovascular bundles. At the time of defect creation, three different types of human cell populations (2.5 × 10 6 cells/0.2 mL: umbilical vein endothelial cells, adipose‐derived stem cells, and amniotic fluid‐derived stem cells) were injected intracavernously into the penile tissue. Saline injection (0.2 mL) served as a control group. Erectile function and histomorphological analyses of penile tissues were assessed 12 weeks after defect creation and cell or saline injection. Results: The ratio of intracavernous pressure to mean arterial pressure (functional indicator) was significantly higher in the cell therapy groups compared to the saline‐injected control group ( P < 0.05). Immunofluorescence staining showed more cells expressing biomarkers of endothelial, smooth muscle, and nerve cells within the penile tissue in the cell therapy groups when compared to the control group. Conclusions: Cell therapy enhanced erectile function and ameliorated the histological changes 12 weeks after pelvic neurovascular injury in vivo, indicating that cell therapy may improve the long‐term outcomes in neurogenic, myogenic and vascular tissue regeneration in the treatment of NVED.